Reservoir engineering handbook - Ahmed, Tarek H., 1946- (Amsterdam ; Boston : Gulf Professional Pub., 2010)
This book provides solid information and insight for engineers and students alike on maximizing production from a field in order to obtain the best possible economic return. This guide contains information on predicting oil reservoir performance through the analysis of oil recovery mechanisms and performance calculations. It also contains valuable information on key relationships among the different operating variables. The examples contained within this reference demonstrate the performance of processes under forceful conditions through a wide variety of applications. Includes new chapters on decline and type curve analysis as well as reservoir simulation and updated material including the liquid volatility parameter, commonly designated Rv. Provides a guide to predicting oil reservoir performance through the analysis of oil recovery mechanisms and performance calculation.
1. Fundamentals of Reservoir Fluid Behavior -- 2. Reservoir-Fluid Properties -- 3. Laboratory Analysis of Reservoir Fluids -- 4. Fundamentals of Rock Properties -- 5. Relative Permeability Concepts -- 6. Fundamentals of Reservoir Fluid Flow -- 7. Oil Well Performance -- 8. Gas Well Performance -- 9. Gas and Water Coning -- 10. Water Influx -- 11. Oil Recovery Mechanisms and the Material Balance Equation -- 12. Predicting Oil Reservoir Performance -- 13. Gas Reservoirs -- 14. Principles of Waterflooding -- 15. Vapor-Liquid Phase Equilibria -- 16. Analysis of Decline and Type Curves -- 17. Fractured Reservoirs.
Includes bibliographical references and index.
Keywords: Oil reservoir engineering; Oil fields; Gas reservoirs; Mining engineering; Engineering; Electronic books